Flexible ultra‐high transformation ratio‐based dual‐band impedance transformer and its applications in a T‐junction power divider. Issue 12 (27th May 2021) - Banerjee, Deepayan; Hashmi, Mohammad; Ghannouchi, Fadhel
Abstract: A design scheme is presented for an all‐pass coupled‐line (APCL)‐based dual‐band impedance‐matching network. Salient features include a highly flexible frequency ratio (r) (high of 15 and low of 1.2) and impedance transformation ratio (k) (high of 9 and low of 0.2) simultaneously at two arbitrary, uncorrelated frequencies of interest. The design strategy consists of two APCL sections and a stub that prove to be simple and easy to prototype. Detailed mathematical modelling and graphical interpretations have been presented. Closed‐form design equations have been developed and backed up with design examples. Two dual‐band T‐junction power dividers (TPDs) have been designed to demonstrate the application of the proposed impedance transformer at two widely separated frequencies. RO4350 B‐ and RO5880‐based prototypes have been fabricated for both the matching network and the TPD to validate the proposed theory. The measurement results demonstrate an achievable frequency ratio of 15 and an impedance transformation ratio of 9 in simultaneous operation mode.